Application of plyometric training: How does it affect throwing strength and speed in handball? - Procopio B. Dafun JR; Joselito M. Custodio (Journal of Applied Movement and Sport Science, 2025)
Background. Handball demands balanced physical abilities in every aspect. Throwing power is one of the key factors in this sport because it plays a role in scoring goals, making passes, and increasing the speed of the game.Objectives. This study aims to analyze the effectiveness of plyometric training on the throwing power of handball athletes.Methods. This study uses an experimental method with a one-group pretest-posttest design. This research was conducted at Mariano Marcos State University, Philippines. The sampling technique used perposive sampling, so that all 15 athletes in the team aged 17-22 years were used as research samples. The treatment given was in the form of plyometric training for 4 weeks with a frequency of three times per week. Data collection was carried out using a strength test with the Medicine Ball Javelin Quadrathlon instrument. Data analysis was carried out with the help of the SPSS version 26 application.Results. Based on data analysis, there is a significant difference between the average pretest score (19.93) and posttest score (22.00), showing an increase of 2.07. The significance test results show a p-value of 0.000 (<0.05), which indicates that plyometric training is significantly effective in increasing strength and throwing speed in handball.Conclusion. The results of this study prove that plyometric training is effective in increasing the strength and speed of a ball throw in handball. Therefore, plyometric training can be applied as a training method to develop the performance of athletes in this sport.